EXPERIMENTAL MORPHOLOGICAL STUDY OF DENTAL PULP LESIONS AT DIFFERENT STAGES OF DENTAL CARIES - Hrynyshyn, O.B.; Dydyk, N.M.; Filenko, B.M. (World of Medicine and Biology, 2020)
Numerous studies show that in the structure of the affection of deciduous teeth by dental caries, a high percentage of complicated dental caries is observed. Paper was aimed at the study of morphological lesion of the dental pulp in experimental dental caries of various severity in rats with theoretical rationale of the principles of treatment of pulpitis. 50 outbred albino male rates were involved into study. Experimental dental caries in rats was induced by special cariesogenic diet. At the first stage, the depth of carious lesions of the enamel and dentin was measured. The second stage was performed on decalcified blocks of teeth, serial sections were made from the resulting blocks, stained with hematoxylin and eosin. It revealed the potential occurrence of more frequent complications in the conservative treatment of deep carious lesions of approximal surfaces in comparison with deep lesions of chewing surfaces. Dental pulp carious lesion depends not only on the degree of carious process, but also on its localization, which should be taken into account when choosing the optimal method of treatment of dental caries, which also prevents the development of its complications.
Keywords: experimental caries; tooth pulp; morphology